Trends in Characteristics and Outcomes in Primary Heart Failure Hospitalizations Among Older Population in the United States, 2004 to 2018. (26th January 2022) - Minhas, Abdul Mannan Khan; Ijaz, Sardar Hassan; Jamal, Shakeel; Dani, Sourbha S.; Khan, Muhammad Shahzeb; Greene, Stephen J.; Fudim, Marat; Warraich, Haider J.; Shapiro, Michael D.; Virani, Salim S.; Nasir, Khurram; Khan, Safi U.
Abstract : Background: Heart failure (HF) accounts for a significant proportion of morbidity, mortality, and health care costs among older adults in the United States. We evaluated trends in clinical outcomes and the economic burden of HF hospitalizations in older patients (≥80 years). Methods: This analysis included data from the National Inpatient Sample between January 2004 and December 2018. We examined the trends of clinical characteristics, inpatient mortality, and health care cost utilization in older US adults for HF hospitalizations. Results: We identified 6 034 951 weighted HF hospitalizations for older adults (3527 per 100 000 person-years). After an initial decline in HF hospitalizations per 100 000 older US older adults from 4211 in 2004 to 3089 in 2014, there was increase to 3388 in 2018 ( P trend <0.001 for both). There was an overall increase in cardiometabolic and chronic comorbidities during the study period. Overall, inpatient mortality was 4.7%; the adjusted inpatient mortality decreased from 6.1% in 2004 to 3.6% in 2018 ( P trend <0.001). There was a decrease in adjusted mean length of stay (from 6.0 days in 2004 to 4.7 days in 2018) and adjusted inflation-adjusted care costs (from $11 865 in 2004 to $9677 in 2018) during the study period ( P trend <0.001 for both). In comparison with younger adults (<80 years), older adults had higher inpatient mortality (4.7% versus 2.2%) but lower inflation-adjusted care costs ($10 587 versus $14 088). Conclusions: This 15-year national data suggests that despite a higher comorbidity burden and the recent increase in hospitalizations for HF in older patients, there has been an encouraging trend towards lower inpatient mortality, health care cost, and hospital length of stay among older adults in the United States.